2007
DOI: 10.1128/jb.01543-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Physiological Responses of Bradyrhizobium japonicum to Desiccation-Induced Stress

Abstract: Line 4 should read ".. . 15 to 20% of the 8,453 B. japonicum open reading frames,. .. ." Page 6753, column 1: In the first full paragraph, the third sentence should end as follows: ".. . for 8,453 predicted B. japonicum ORFs." Page 6753, column 2: The following paragraph should appear before Results. Microarray data accession number. All of the microarray data have been deposited in Gene Expression Omnibus (http://www .ncbi.nlm.nih.gov/geo/) and are available via accession number GSE9125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 0 publications
6
92
0
Order By: Relevance
“…Indeed, studying Saccharomyces cerevisiae, Benaroudj et al (2001) showed that in addition to its structural function in desiccation tolerance, trehalose accumulates during cellular stress (exposure to mild heat shock at 38 1C or to a proteasome inhibitor) and markedly protects cells and proteins from damage generated from an oxygen radical-generating system (that is, H 2 O 2 and FeCl 3 through the Fenton reaction). A similar role was suggested by Cytryn et al (2007) who studied the desiccation-induced stress in the a-proteobacterium Bradyrhizobium japonicum.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, studying Saccharomyces cerevisiae, Benaroudj et al (2001) showed that in addition to its structural function in desiccation tolerance, trehalose accumulates during cellular stress (exposure to mild heat shock at 38 1C or to a proteasome inhibitor) and markedly protects cells and proteins from damage generated from an oxygen radical-generating system (that is, H 2 O 2 and FeCl 3 through the Fenton reaction). A similar role was suggested by Cytryn et al (2007) who studied the desiccation-induced stress in the a-proteobacterium Bradyrhizobium japonicum.…”
Section: Discussionmentioning
confidence: 80%
“…However, we did not detect TreS activity when the organism was grown on maltose. It is also possible that these pathways may be activated by other environmental stimuli such as desiccation, which induces Tps/Tpp and TreS in Bradyrhizobium japonicum (6).…”
Section: Discussionmentioning
confidence: 99%
“…Cells carrying pET30b-tps, pET30b-tpp, or pET11a-treT were grown to an optical density at 610 nm of 1.0 at 37°C in LB medium (2 liters) containing kanamycin (30 g/ml) or ampicillin (100 g/ml) for selection, and IPTG (isopropyl-␤-D-thiogalactopyranoside) (1 mM) was added to induce gene expression. Cells carrying (His) 6 -Tps and (His) 6 -Tpp were allowed to grow for ϳ6 h, harvested, and suspended in 20 mM sodium phosphate buffer with 0.5 M NaCl and 10 mM MgCl 2 , DNase (4 g/ml), and a protease inhibitor cocktail (Roche). Cells carrying the recombinant TreT were allowed to grow for a further 10 h at 30°C, suspended in 20 mM Tris-HCl at pH 7.6, and disrupted in a French pressure cell, and debris was removed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analysis of B. japonicum USDA110 in response to desiccation stress showed that a number of genes responsible for proteins involved in membrane protection, repair of DNA damage, stability of proteins and oxidative stress reduction were upregulated when compared to hydrated cells (Cytryn et al, 2007). They also reported that the number of genes upregulated by osmotic stress were significantly fewer than those upregulated by desiccation stress.…”
Section: Desiccation Tolerance Mechanismsmentioning
confidence: 95%
“…A study reporting on the response of B. japonicum USDA 110 to desiccation stress identified several genes related to synthesis of LPS that are upregulated in response to desiccation (Cytryn et al, 2007). The LPS of R. leguminosarum bv.…”
Section: Desiccation Tolerance Mechanismsmentioning
confidence: 99%